2022
DOI: 10.3389/fcvm.2022.956627
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation in patients with ventricular fibrillation by purkinje de-networking

Abstract: BackgroundVentricular fibrillation (VF) is a leading cause of cardiovascular death worldwide. However, recurrence rates of arrhythmia are high leading to mortality and morbidity. Recently, Purkinje fibers have been identified as potential sources of VF initiation and maintenance.AimThe study analyzes the feasibility and effectiveness of catheter ablation in patients with recurrent VF by specific Purkinje de-networking (PDN).MethodsConsecutive patients with recurrent VF undergoing PDN were included in this obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, it has been reported that 25% of patients who undergo catheter ablation for VF using PDN develop cLBBB. 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that 25% of patients who undergo catheter ablation for VF using PDN develop cLBBB. 3 …”
Section: Discussionmentioning
confidence: 99%
“… 2 However, while PDN may be relatively easy to perform, it poses a risk of complete left bundle branch block (cLBBB), as seen in a previous study where 25% of patients developed new cLBBB during PDN. 3 In this report, we describe a patient with a drug-refractory VF storm following ACS under Impella support in whom we successfully performed PDN using the ripple map (RM) feature integrated into the CARTO 3 system (Biosense Webster, Diamond Bar, CA) to identify the bifurcation of the main left bundle into the left anterior and posterior fascicles.…”
Section: Introductionmentioning
confidence: 99%
“…If challenging cases arise where there is an absence of trigger PVCs and low-voltage areas representing scar or fibrosis, Purkinje de-networking can be considered as an alternative. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, “Purkinje de-networking” has emerged as an optional treatment of VF. 7 The strategy proposed is to ablate all Purkinje potentials between LAF and LPF in the sense of tissue homogenization. The triggering PVC in the present case could have been treated with this technique because it is likely that the success site as well as the conducting pathway to the exit of the PVC were included within this target region.…”
Section: Discussionmentioning
confidence: 99%